Study of endoscopic esophageal variceal ligation cases in Tishreen University Hospital - Alhaddad, Seraj Elias; Zeizafoun, Hassan; Intanious, Milad (Journal of medical and pharmaceutical sciences, 2021)
Objective: The aim of this study is to estimate the effectiveness and complications of performing EVL in cirrhotic patients, and to assess the outcome of rebleeding events after EVL. Patients and Methods: An Observational Descriptive Study conducted for the period from January 2020 to January 2021 at Tishreen University Hospital in Lattakia- Syria, 45 Cirrhotic patients with esophageal varices who underwent 69 EVL sessions whether done as prophylactic or therapeutic followed up for three weeks. Results: The median age was 57 years, 66.70% of patients were male. The most common etiology was cryptogenic cirrhosis (40%), and 44.4% of patients had esophageal varices grade III. The most common indication for performing EVL was primary prophylaxis (46.4%). Initial control of bleeding was achieved in 95.2% of emergency procedures. The mortality rate during follow- up was 2.2%. Chest pain was the most common complication of EVL (31.9%). The incidence of re- bleeding events after EVL was 7.24%, more frequently in emergency procedures. Re- bleeding was significantly associated with alcoholic liver disease, poor liver condition (Child- Paugh C class), emergency procedures, coagulation disorders (low levels of PLT and high levels of INR) and presence of large varices (grade III and IV). Conclusion: EVL is feasible, safe, and effective for the management of esophageal varices in patients with end stage liver disease.